2008
DOI: 10.1055/s-2007-1012107
|View full text |Cite
|
Sign up to set email alerts
|

Sonographie des Abdomens als Screeningmethode*

Abstract: Abdominal ultrasonic screening of patients clinically asymptomatic of abdominal disease was performed in 5 720 subjects. In these asymptomatic persons pathological ultrasonic findings were reported in 47.1% of all cases, but these were mostly without clinical relevance. This is especially true for diffuse liver disease (30.9%), asymptomatic gallstones (6.1%), and typical renal cysts (5.7%). Asymptomatic malignant abdominal tumours (0.2% or 13 cases) were detected very rarely, and were found to be mostly renal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
6

Year Published

2008
2008
2013
2013

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 0 publications
0
1
0
6
Order By: Relevance
“…Der Terminus .U lt rascha llscree ning des Abdomens" wird unterschiedlich verwendet [13]. Basierend auf Kremer et al [13]…”
Section: Begriffsbestimmungunclassified
See 3 more Smart Citations
“…Der Terminus .U lt rascha llscree ning des Abdomens" wird unterschiedlich verwendet [13]. Basierend auf Kremer et al [13]…”
Section: Begriffsbestimmungunclassified
“…Auch die Forderung der Untersuchung des gesamten Abdomens bei spezifischer Organfragestellung [13] ist nicht uneingeschrankt zu unterstiitzen. Es ist sicherlich sinnvoll und von einem arztlichen Standpunkt aus auch zu fordern, die Nieren (in der Fragestellung Tumor) und die abdominelle Aorta (in der Fragestellung Aneurysma) zu untersuchen.…”
Section: Schhnsfolqerunqunclassified
See 2 more Smart Citations
“…In a screening study, renal cysts were found in 5.4% of the population [2]. SRC prevalence increases with age, being 20% in individuals at 40 years and 33% in those older than 60 years [3].…”
Section: Introductionmentioning
confidence: 99%